Lima Barreto, Drummond e Plínio Marcos: crônicas, futebol e identidade nacional - Florenzano, Giulia Catarina (2019)
This dissertation proposes an analysis on the construction of the Brazilian national identity linked to football through the chronicles of Lima Barreto (1881-1922), Carlos Drummond de Andrade (1902-1987) and Plínio Marcos (1935-1999). Among its objectives: the reflection on the irony and other language resources in the process of the Brazilian identity construction, in addition to apprehend points of tension and harmony in the development of the national identity linked to football. In order to achieve these objectives, the dissertation is guided by the following problematization: how does irony reveal faces of the national identity in the football chronicles of Lima Barreto, Drummond and Plínio Marcos? How does the Brazilian identity inscribed in the chronicles imply social relations between football, art and criticism? We sustain the proposition that language resources, such as sarcasm, grotesque, hyperbole, antithesis, colloquialism and, specially, irony, and the artistic configurations of the trickster, ginga and dance, inscribe in the chronicles, forming relations between literature, society and football. Besides that, the football chronicles reveal inequalities in the Brazilian democracy, marking the national identity. Theoretical foundation is based on the reflections of Roberto DaMatta (1982), Gilberto Freyre (1945), Jorge de Sá (1985), André Mendes Capraro (2007), Ítalo Calvino (1990), Lélia Parreira Duarte (2006), Elcio Loureiro Cornelsen (2006), Leonardo Affonso de Miranda Pereira (2000), Cláudia Mattos (1997), Paulo Henrique do Nascimento (2008), Mario Filho (2003) Gilberto Agostino (2002) and José Paulo Florenzano (2009). Among other considerations, this research reveals that irony, in the context of these football chronicles, besides denouncing socio-political-cultural relations, offers another understanding to these same relations, since it is based on a critical-creative set, indispensable to overcome limitations and determinisms